A Complex Systems Perspective of Communication from Cells to Societies - Berea, Anamaria (IntechOpen, 2019)
This book is an interdisciplinary effort to understand the evolution of communication from cells to societies, both in living organisms and in non-living ones, such as designed or emergent systems from socio-technological innovations (i.e., digital communication, institutional communication). It aims to provide better understanding of the universal versus contextual patterns of communication that we can potentially classify and identify if we look deeper into the history and evolution of this phenomenon at large. Novel research from a variety of disciplines, such as information theory, biology, linguistics, culture and social science that take a complex perspective is being explored, for an integrated understanding of what communication is at a fundamental level.